Development of an in vitro Microtuberization and Temporary Immersion Bioreactor System to Evaluate Heat Stress Tolerance in Potatoes (Solanum tuberosum L.) - Gautam, Sanjeev; Solis-Gracia, Nora; Teale, Megan K.; Mandadi, Kranthi; Silva, Jorge A. da; Vales, M. Isabel (Frontiers in Plant Science, 2021)
High temperature (heat) stress reduces tuber yield and quality of potatoes. Screening potatoes for heat tolerance is increasingly important, considering the climate change scenario and expansion of potatoes to countries where heat stress is an issue. In vitro screening for tolerance to abiotic stresses offers several advantages, including quick evaluation of numerous genotypes (clones) in reduced space, controlled environmental conditions (temperature and photoperiod), and free from confounding variables inherent to greenhouse and field conditions. In this study, we explored the feasibility of using a temporary immersion bioreactor system for heat tolerance screening of potatoes. We determined the best hormone-free microtuberizing media for this system (MSG with 8% sucrose) to enhance microtuber number and size. Comparisons of microtubers produced at 30 °C as heat treatment, with 16 °C as normal condition, allowed to identify heat tolerant and susceptible potato clones. The use of bioreactors allowed distinguishing well-formed (non-deformed) from deformed microtubers. Heat stress increased the total biomass of plant tissues in all the clones. However, the effect of heat stress on microtuber number and weight varied among the clones. Incubation at 30 °C decreased the weight and number of non-deformed microtubers in all the clones except for Reveille Russet in which the weight of non-deformed microtubers was significantly increased and the count of non-deformed microtubers was not affected. The potato variety Reveille Russet, which was selected under high-temperature field conditions in Texas, had many non-deformed microtubers per explant and the highest microtuber weight among four clones evaluated under heat stress. We described a faster and reliable in vitro microtuberization system for abiotic stress tolerance screening, identified Reveille Russet as a promising heat-tolerant potato variety, and confirmed Russet Burbank and Atlantic as susceptible heat-tolerant checks.